THE USE OF SELF-TALK STRATEGY IN TEACHING WRITING RECOUNT TEXTS - Safarullah, Thesar; Sutapa Y, Y. Gatot; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to find out the effectiveness of self-talk strategy in teaching writing recount texts to Year – 8 students of SMPN 18 Pontianak in Academic Year 2017/2018. The population of this research was all of Year – 8 students of SMP Negeri 18 Pontianak in Academic Year 2017/2018. The writer took the sample by using cluster random sampling to determine the participant of research which is consisted of 36 students. The data were collected by using measurement technique and the tool of data collection was written test. Referring to the research findings, the data showed that the effect size of treatment was 2.208. It was categorized as a strong effect (ES > 0.8). Thus, the writer positively recommends the teacher to use self-talk as a variation of strategy in teaching process, especially in the teaching writing recount texts.Key Words: Self-Talk Strategy, Recount Texts, Writing.